2019
DOI: 10.1007/s42399-019-00188-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Deep Vein Thrombosis in Type 2 Diabetics with Biopsy-Proven Non-alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) can lead to a prothrombotic stage increasing the risk of deep vein thrombosis (DVT). We aimed to assess the prevalence and factors associated with DVT in patients with type 2 diabetes (T2D) and biopsy-proven NAFLD. Using ICD-codes, all T2D patients who had liver biopsy done for suspected NAFLD were identified and assessed. Patients with secondary causes of hepatic steatosis (Hepatitis, excess alcohol, etc.) were excluded. Liver biopsy was staged as F0-4, advanced fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Studentized residual tests, Buajat plot and r diagnostic tests for influential studies confirmed three studies [3,21,25] significantly influenced the incidence meta-analysis results (SP-Fig. 6), and two studies [28,48] prevalence meta-analysis results (SP-Fig.…”
Section: Outlier Studiesmentioning
confidence: 65%
See 4 more Smart Citations
“…Studentized residual tests, Buajat plot and r diagnostic tests for influential studies confirmed three studies [3,21,25] significantly influenced the incidence meta-analysis results (SP-Fig. 6), and two studies [28,48] prevalence meta-analysis results (SP-Fig.…”
Section: Outlier Studiesmentioning
confidence: 65%
“…After screening of titles and abstracts, 84 studies were selected for further search, 29 studies [3,12,14,17,[21][22][23][24][25][26][27][28][29][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] reporting incidence or prevalence of VTE in CLD were included (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations